2013
DOI: 10.3390/ijms141223533
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of the Main Active Anticancer Alkaloids from the Root of Glaucium flavum

Abstract: Glaucium flavum is used in Algerian folk medicine to remove warts (benign tumors). Its local appellations are Cheqiq el-asfar and Qarn el-djedyane. We have recently reported the anti-tumoral activity of Glaucium flavum root alkaloid extract against human cancer cells, in vitro and in vivo. The principal identified alkaloid in the extract was protopine. This study aims to determine which component(s) of Glaucium flavum root extract might possess potent antitumor activity on human cancer cells. Quantitative esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 17 publications
1
23
0
3
Order By: Relevance
“…Moreover, Arafa et al (2016) reported that ethanol extracts from the aerial parts of the plant possessed analgesic, antibacterial, anti-inflammatory, antifungal and cytotoxic activities. Similarly, Hadjiakhoondi et al (2013) observed that the aerial parts alkaloid extracts exhibited cytotoxic effects against colon adenocarcinoma cell lines (HT-29, Caco-2), while Bournine et al (2013) reported that the root methanolic extracts displayed anticancer effects against breast cancer cells. Other health effects include depressive effects of various plant parts extracts on the central nervous system (CNS) and blood glucose levels (Cabo et al, 1988(Cabo et al, , 1987, while the main bioactive compound of the species (glaucine) has been associated with various pharmacological properties, such as antitussive, antiparkinsonic, hypotensive, antiviral, cardiovascular and cytotoxic effects (Orallo et al, 1995;Spasova et al, 2008).…”
Section: Health Effectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Arafa et al (2016) reported that ethanol extracts from the aerial parts of the plant possessed analgesic, antibacterial, anti-inflammatory, antifungal and cytotoxic activities. Similarly, Hadjiakhoondi et al (2013) observed that the aerial parts alkaloid extracts exhibited cytotoxic effects against colon adenocarcinoma cell lines (HT-29, Caco-2), while Bournine et al (2013) reported that the root methanolic extracts displayed anticancer effects against breast cancer cells. Other health effects include depressive effects of various plant parts extracts on the central nervous system (CNS) and blood glucose levels (Cabo et al, 1988(Cabo et al, , 1987, while the main bioactive compound of the species (glaucine) has been associated with various pharmacological properties, such as antitussive, antiparkinsonic, hypotensive, antiviral, cardiovascular and cytotoxic effects (Orallo et al, 1995;Spasova et al, 2008).…”
Section: Health Effectsmentioning
confidence: 95%
“…1c). Moreover, Bournine et al (2013) studied the chemical composition of roots and isolated two new alkaloids, namely protopine and bocconoline. Two more alkaloids were also isolated and identified in aerial parts as N,N-dimethyl-hernovine and sanguinarine (Och et al, 2017).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Previously detected BIAs generally belong to the protopine, benzophenanthridine, or aporphine subgroups. HPLC-UV analysis showed that glaucine predominates in aerial organs, whereas protopine occurs mostly in roots (Bournine et al, 2013). Isocorydine, an aporphine alkaloid with one free hydroxyl group, has also been reported in G. flavum (Daskalova et al, 1988;Peled et al, 1988;Kintsurashvili and Vachnadze 2000;Petitto et al, 2010;).…”
Section: Preferred (Rs)-6-o-laudanosoline and (Rs)-6-omethyllaudanomentioning
confidence: 99%
“…As a result, we suggest that H. lupulus extracts at high concentration might have an effect on the viability of human colon cancer cells with a similar anti-apoptotic and/or an antioxidant mechanisms. To explain certain mechanism(s) of this potential dual role of H. lupulus on survival and growth of the cancer cells, and to precise cut off value and concentration limits of H. lupulus extracts before its use as an anti-neoplastic agent will need some further studies 26 .…”
Section: Cell Cytotoxicity Assay Of H Lupulus Extractsmentioning
confidence: 99%